106k views
1 vote
Given f(x) = X-1/2
solve for f1(5).

Given f(x) = X-1/2 solve for f1(5).-example-1
User Amuniz
by
5.6k points

2 Answers

6 votes

as you already know, we start off by doing a quick switcheroo on the variables in order to get the inverse of any expression.


\bf \stackrel{f(x)}{y}=\cfrac{x-1}{2}\implies \stackrel{switcheroo}{x=\cfrac{y-1}{2}}\implies 2x=y-1\implies 2x+1=\stackrel{f^(-1)(x)}{y} \\\\\\ 2(5)+1=^(-1)(5)\implies 11=f^(-1)(5)

User Nozim Turakulov
by
5.0k points
4 votes

Answer:

11

Explanation:

To find the inverse let y = f(x) and rearrange making x the subject, that is

y =
(x-1)/(2) ( multiply both sides by 2 )

2y = x - 1 ( add 1 to both sides )

2y + 1 = x

Change y back into terms of x, thus


f^(-1)(x) = 2x + 1 and


f^(-1)(5) = 2(5) + 1 = 10 + 1 = 11

User Eddie
by
5.8k points